Occupational Therapy Practice Framework: Domain and Process-Fourth Edition (The American journal of occupational therapy, 2020)
The fourth edition of the Occupational Therapy Practice Framework: Domain and Process (hereinafter referred to as the OTPF-4), is an official document of the American Occupational Therapy Association (AOTA). Intended for occupational therapy practitioners and students, other health care professionals, educators, researchers, payers, policymakers, and consumers, the OTPF-4 presents a summary of interrelated constructs that describe occupational therapy practice.The fourth edition of the Occupational Therapy Practice Framework: Domain and Process (hereinafter referred to as the OTPF-4), is an official document of the American Occupational Therapy Association (AOTA). Intended for occupational therapy practitioners and students, other health care professionals, educators, researchers, payers, policymakers, and consumers, the OTPF-4 presents a summary of interrelated constructs that describe occupational therapy practice.